(untitled) (Mustansiria Dental Journal, 2018)
Aims: This study was conducted to assess the epidemiology and some of the possible risk factors causing cleft lip and palate in Erbil city. Materials and Methods: the data were obtained from the records of Raparin paediatric and maternity hospital in the center of Erbil city. The file records of live births during a period from January 2000 to January 2008 were reviewed for the occurrence of cleft lip and palate. The cleft cases were evaluated for site and type of cleft and sex of the infant. and some risk factors. Results: 121 cleft lip and/or palate cases out of 60418 live births were registered. The overall incidence was 2:1000 live births. The percentage of cleft lip and palate, cleft palate only, cleft lip only was 55%, 30%, and 15% respectively. The ratios with respect of left or right or bilateral cleft was approximately 4.5:2:1.The infant sex and site of family residence showed no significant influence on the incidence of clefting. Maternal age of more than 30 years, maternal smoking, and positive family history of clefts, consanguineous marriage and low infant birth weight significantly increased the incidence of cleft lip and palate. About 7.4% of cleft cases were associated with other congenital anomalies, most frequently congenital heart disease. Conclusion: The incidence of cleft lip and/or cleft palate is 2:1000 births. The incidence of cleft lip and palate is two times greater than cleft palate alone, and three times than cleft lip alone. Cleft lip was two times greater on the left side than on the right side. The incidence of clefts was greater in males than females.